Beleza Natural, comunidade virtual e atores - Simões, Roberta Caldas (2010)
Virtual communities or on-line communities, as is known, are increasingly present in our daily society. They promote and facilitate the reinvention of many social practices have institutionalized such as relate and communicate, educate, consuming, among o